Kadar Apolipoprotein B dan Aterosklerosis Arteri Karotis Interna pada Pasien Pasca Stroke Iskemik - Haryo Teguh; Retnaningsih Retnaningsih; MI Widiastuti (MEDIA MEDIKA INDONESIANA, 2011)
ABSTRACTRelations between apolipoprotein B level with internal carotid artery atherosclerosis in post ischemic stroke patientBackground: Ischemic stroke is caused by brain artery obstruction or brain artery narrowing called atherosclerosis. Its marker is the thickness of tunica intima-media (intima-media thickness/IMT) of the artery. Apolipoprotein B is one of the indicator of atherosclerosis diseases. Most of the previous studies investigate association between apolipoprotein B level and cardiovascular disease, while the association between apolipoprotein B and atherosclerosis in post ischemic stroke patients has not been studied yet.Objective: To investigate association between apolipoprotein B level and internal carotid artery atherosclerosis based on thickness of intima-media in patients post ischemic stroke.Method: This cross-sectional study was done in post ischemic stroke (first attack) subjects in outpatient clinic of Neurology Department Kariadi Hospital Semarang, during December until February 2011. Apolipoprotein B level was measured with Integra method, during 1 month after the onset. The thickness of tunica intima-media of the internal carotid artery was measured by Ultrasonography Duplex.Result: Fourty four patients post ischemic stroke that met the inclusion and exclusion criteria, comprise of 22 male (50%) and 22 female (50%). Atherosclerosis which was defined as tunica intima-media thickness >0.9 mm, was found in 24 subjects (54.6%). Apolipoprotein B level, which designated as high if apoB >105 mg/dl, was found in 25 subjects (56.8%). Multivariate logistics regression test controlling lipid factor as confounding factors resulted in OR 142.1 (p=0.0001).Conclusion: Apolipoprotein B level significantly correlate with atherosclerosis of internal carotid artery represented by thickness of intima-media in patients post ischemic stroke.Keywords: Apolipoprotein B level, internal carotid artery atherosclerosis, ischemic strokeABSTRAKLatar belakang: Stroke iskemik disebabkan obstruksi atau penyempitan pembuluh darah arteri otak yang disebut aterosklerosis. Marker aterosklerosis adalah ketebalan tunika intima-media (intima-media thickness/IMT) di pembuluh darah tersebut. Kadar apolipoprotein B merupakan indikator penyakit yang disebabkan aterosklerosis. Penelitian yang ada kebanyakan menghubungkan pengaruh apoB dengan penyakit kardiovaskuler, pengaruh apoB dengan aterosklerosis pada pasien pasca stroke iskemik belum pernah dilakukan.Tujuan: Membuktikan adanya hubungan antara kadar apolipoprotein B dengan aterosklerosis arteri karotis interna yang dilihat dari ketebalan tunika intima-media pada pasien pasca stroke iskemik.Metode: Penelitian cross sectional, dilaksanakan di Poli Saraf RSUP Dr. Kariadi Semarang, periode Desember 2010-Februari 2011. Subyek penelitian adalah pasien pasca stroke iskemik pertama kali yang diambil secara consecutive sampling. Kadar apolipoprotein B diukur dengan menggunakan metode Integra, pemeriksaan ketebalan tunika intima-media arteri karotis internamenggunakan Ultrasonografi Duplek.Hasil: Empat puluh empat pasien pasca stroke iskemik yang memenuhi kriteria inklusi dan eksklusi, terdiri dari pria 22 (50,0%) dan wanita 22 (50,0%). Dikategorikan aterosklerosis bila ketebalan tunika intima-media >0,9 mm dan terjadi pada 24 subyek (54,6%). Kadar apolipoprotein B tinggi (apoB>105 mg/dl) terdapat sebanyak 25 subyek (56,8%). Hasil analisis uji regresi logistik multivariat yang mengendalikan faktor lipid (kolesterol, LDL, trigliserid) menunjukkan OR 142,1 (p=0,0001).